2009
DOI: 10.1128/aem.02633-08
|View full text |Cite
|
Sign up to set email alerts
|

Climate and Tick Seasonality Are Predictors of Borrelia burgdorferi Genotype Distribution

Abstract: The blacklegged tick, Ixodes scapularis, is of significant public health importance as a vector of Borrelia burgdorferi, the agent of Lyme borreliosis. The timing of seasonal activity of each immature I. scapularis life stage relative to the next is critical for the maintenance of B. burgdorferi because larvae must feed after an infected nymph to efficiently acquire the infection from reservoir hosts. Recent studies have shown that some strains of B. burgdorferi do not persist in the primary reservoir host for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
179
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 152 publications
(191 citation statements)
references
References 57 publications
(75 reference statements)
12
179
0
Order By: Relevance
“…Previous reports of higher prevalence in eastern Europe seem to be the result of studies examining small numbers of ticks, which may be adequate for the local assessment of the presence of B. burgdorferi sensu lato but unsatisfactory for the appraisal of prevalence patterns in a wide area. One of the most relevant results of our study was the relationship between abiotic traits and the prevalence of B. burgdorferi sensu lato in nymphal ticks, uncovering a relationship between prevalence and temperature already suggested in previous studies (14,26). Thus, environmental features of the Western Palearctic region are linked to the geographic pattern of variation in B. burgdorferi sensu lato prevalence in ticks.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Previous reports of higher prevalence in eastern Europe seem to be the result of studies examining small numbers of ticks, which may be adequate for the local assessment of the presence of B. burgdorferi sensu lato but unsatisfactory for the appraisal of prevalence patterns in a wide area. One of the most relevant results of our study was the relationship between abiotic traits and the prevalence of B. burgdorferi sensu lato in nymphal ticks, uncovering a relationship between prevalence and temperature already suggested in previous studies (14,26). Thus, environmental features of the Western Palearctic region are linked to the geographic pattern of variation in B. burgdorferi sensu lato prevalence in ticks.…”
Section: Discussionmentioning
confidence: 51%
“…Recently, OspA serotype 4 of B. garinii has been associated with a new species, Borrelia bavariensis (30). Some studies have indicated the influence of tick life cycle traits on the distribution of B. burgdorferi sensu stricto genotypes in the United States as a consequence of different climate patterns affecting tick phenology (14). A temperatureregulated pattern of B. burgdorferi sensu stricto genotypes in the United States has been interpreted as the control of the synchrony of the activity of the different tick stages by the yearly temperature amplitude and persistence of the pathogen in the primary reservoir host (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, transport of B. burgdorferi between northeastern and midwestern I. scapularis populations appears to be relatively infrequent. Regional isolation of B. burgdorferi genotypes may have epidemiological implications due to differences in clinical outcomes associated with specific genotypes (51)(52)(53)(54)(55).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in North America have shown that the host-seeking phenologies of the primary vectors of Lyme disease spirochetes-the nymphal stages of Ixodes scapularis Say in the east and Ixodes pacificus Cooley and Kohls in the far west-are strongly associated with environmental variables (Lane et al 1995;Vail and Smith 1998;Eisen et al 2002Eisen et al , 2003Eisen et al , 2016Diuk-Wasser et al 2006;Gatewood et al 2009). …”
mentioning
confidence: 99%